ANALISIS PENGARUH PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA KUD TRIKARYA KARANG TENGAH KECEMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR - Mardiansyah, Reza; Solikhan, Solikhan (Jurnal Trisna Riset, 2025)
Village Unit Cooperatives are cooperatives in rural areas that are engaged in providing community needs related to the community economy. Village unit cooperatives also have an important role, namely increasing production, helping to improve the economy of village communities and improving the economy of members. This research aims to analyze the effect of service on consumer satisfaction at KUD Trikarya Karang Tengah, East Buay Madang District, East OKU Regency. Good service is an important factor in increasing consumer satisfaction, which ultimately influences customer loyalty and trust in a business. Service variables in this research include speed, accuracy, friendliness and comfort in providing services to consumers. The research method used is a quantitative method with data collection techniques through observation, interviews and questionnaires. Data analysis uses correlation tests and hypothesis tests to determine the extent of the relationship between service and consumer satisfaction. From the results of the hypothesis test calculations, it can be seen that the calculated t value is 2.039, while the t table value at the 95% confidence level for (n-2) is 1.860. So it can be seen that the calculated t value is 2.039 which is greater than the t table, namely = 1.860. Thus Ha is accepted and Ho is rejected. With this calculation it can be concluded that the influence of service on consumer satisfaction is moderate. The results of analysis and hypothesis testing also prove that service has a significant influence on consumer satisfaction. The conclusion of this research is that good service can increase consumer satisfaction at KUD Trikarya Karang Tengah. Therefore, KUD needs to continue to improve service quality in order to maintain and increase customer satisfaction and loyalty.